Sheikh Mohammad Abdullah : Tragic Hero of Kashmir - Bhattacharjea, Ajit (New Delhi Lotus collection/Roli Books, 2008)
Biography of Sheikh Mohammad Abdullah, 1905-1982, former chief minister of Jammu and Kashmir, India.
Include Illustrations, Appendices, Bibliography and Index.
Tragic Hero of Kashmir.
Keywords: Politicians -- India--Jammu and Kashmir -- Politics and government